The Psychological Impact of the COVID-19 Pandemic on Pregnant Women - Raguraman, S.; Muhunthan, K. (Journal of South Asian Federation of Obstetrics and Gynaecology, 2023)
Background: Pregnancy is the most crucial phase of a woman’s life in which she experiences many physical and psychological changes. Women will experience some level of stress and anxiety during this period mainly due to focus on the baby’s health, fear of birthing experience, and adverse obstetric outcomes. Pregnant women are one of the vulnerable populations to psychological impact during this period of the coronavirus disease-2019 (COVID-19) outbreak. Aim: To assess the psychological impact of the COVID-19 pandemic and associated sociodemographic factors among pregnant women attending prenatal clinics and delivering at the University Professorial Unit – Teaching Hospital Jaffna. Methodology: It was a hospital-based descriptive cross-sectional study on the psychological impact of the COVID-19 pandemic among pregnant women, conducted at Teaching Hospital Jaffna from July 2021 to July 2022 among 268 pregnant women attending the prenatal clinic and delivering at Teaching Hospital Jaffna. Results: The study included 217 participants, and the response rate was 80.97%. The majority of the participants (64.5%) fell in the age category of 20–30 years, most of the participants (99%) were Sri Lankan Tamils in ethnicity, and 77.4% were Hindus. Nearly half of the participants (47.5%) completed their General Certificate of Education O level (GCE O/L), and most (81.1%) of them were unemployed. About half of the participants had psychological impact due to the COVID-19 pandemic and were concerned about their prenatal, intrapartum, and postnatal care. Among them, more than three-quarters (77%) of them had anxiety about their prenatal care, about 61% of them had anxiety about labor and intrapartum care; only 46.1% had anxiety about postnatal care. The present study shows that age and educational level are statistically significant (p < 0.05) factors influencing psychological impact among mothers regarding prenatal care. Educational levels also had a statistically significant (p< 0.05) influence on the psychological impact regarding labor and intrapartum care as well as postnatal care among mothers. Conclusion: There is a psychological impact on pregnant women due to COVID-19 regarding their pregnancy care. Hence, it is vital to give attention to the mental status of pregnant women, especially during pandemic situations like COVID-19.
Keywords: Anxiety; Coronavirus disease-2019; Psychological impact